2022
DOI: 10.1155/2022/2810794
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Acupoint Stimulation Ameliorates Cognitive Function through PINK1/Parkin Mediated Mitophagy in VD Rats

Abstract: In this study, we investigated whether transcutaneous electrical acupoint stimulation (TEAS) could improve cognitive function in VD rats by regulating PINK1/Parkin-mediated mitophagy. VD rat model was prepared by modified 2-vessel occlusion (2-VO) and randomly divided into four groups: Sham group (Sham), Model group (Model), TEAS group (TEAS), and TEAS + 3-MA group (T +3 -MA). In the T +3 -MA group, autophagy inhibitor (3-MA) was injected into the lateral ventricle. After modeling, Y maze (YM), new object reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It has shown that TEAS reduced the values of S100β at the end of surgery and 1 day after surgery, and the values of IL-6 on the 1st postoperative day ( Gao et al, 2018 ). TEAS could reduce hippocampal neurons apoptosis by increasing the Bcl-2/Bax ratio and inhibiting activated caspase-3 expression, and improve mitophagy by upregulating PINK1, Parkin, and LC3-II expression and downregulating LC3-I and p62 expression ( Hu et al, 2022 ). Similar to acupuncture, TEAS may also improve cerebral blood flow and brain metabolism, alleviate perioperative hypotension, reduce anesthetic and analgesic consumption, and improve sleep disorders ( Ho et al, 2020 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has shown that TEAS reduced the values of S100β at the end of surgery and 1 day after surgery, and the values of IL-6 on the 1st postoperative day ( Gao et al, 2018 ). TEAS could reduce hippocampal neurons apoptosis by increasing the Bcl-2/Bax ratio and inhibiting activated caspase-3 expression, and improve mitophagy by upregulating PINK1, Parkin, and LC3-II expression and downregulating LC3-I and p62 expression ( Hu et al, 2022 ). Similar to acupuncture, TEAS may also improve cerebral blood flow and brain metabolism, alleviate perioperative hypotension, reduce anesthetic and analgesic consumption, and improve sleep disorders ( Ho et al, 2020 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%